CODE-SWITCHING AND CODE-MIXING IN THE TAPIS PODCAST EPISODE “BAHASA LAMPUNG MILIK SIAPA?” A SOCIOLINGUISTIC ANALYSIS OF MULTILINGUALISM IN LOCAL BROADCASTING MEDIA - Mei Fatmila Sari; Muhammad Ramdhan Fathin Al Farabi; Andriansyah; Nabila Hasri Ainun; Septia Uswatun Hasanah; Detia Aulia Oktarina (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
Abstract: Code-switching and code-mixing are linguistic phenomena commonly observed in multilingual communities, including in digital media that address regional cultural issues. This study examines the forms, types, and factors influencing code-switching and code-mixing in the Tapis Podcast episode “Bahasa Lampung Milik Siapa?” broadcast on TVRI Lampung. A descriptive qualitative approach was employed, with data gathered through listening, recording, note-taking, and verbatim transcription of the speech produced by the host and guest speaker. The classification of code-switching and code-mixing forms draws on Suwito's (1985) theoretical framework, while the contributing factors are analyzed according to Nababan (1984, 2021) and Fishman (1972). The findings reveal that all identified instances of code-switching were internal. Code-mixing, meanwhile, took the form of outer code-mixing into English and Arabic, as well as inner code-mixing into the Lampung language. At the formal linguistic level, single words constituted the most dominant form of code-mixing, followed by hybrid blends (basters), phrases, and idioms. Topic of conversation and speaker-related factors emerged as the primary triggers of both phenomena. Taken together, these findings suggest that multilingual practices in podcasting not only reflect global linguistic influences but also serve as a vehicle for speakers to assert local identity. Culturally grounded podcasts thus carry significant potential as media that support the preservation and revitalization of regional languages in the digital era.